Cancer incidence and mortality in Kathmandu valley in 2018: Kathmandu; Lalitpur; Bhaktapur. (2019)
SUMMARY: BACKGROUND: Nepal Health Research Council (NHRC), a national apical body of Government of Nepal, responsible for promoting scientific study and quality health research in the country, has started Population Based Cancer Registry (PBCR) in Nepal since January 2018. Starting with the Kathmandu Valley, the PBCR has been expanded to other 6 districts with a total of three registries in order to obtain representative information of the country on cancer incidence. The Kathmandu valley cancer registry covers the population of Kathmandu, Bhaktapur and Lalitpur districts of Province 3, whereas the other registries are established in provinces 2, 5 and 6 (Karnali).The objective of Kathmandu valley PBCR is to generate evidence on cancer incidence, patterns and trends of disease and mortality related to cancer in the Kathmandu valley, and to enhance national capacity for sustainable PBCR in Nepal. The NHRC is working in close collaboration with Ministry of Health and Population (MoHP) and WHO to establish the registrie in Nepal that has been technically supported by International Agency for Research on Cancer (IARC). The council has made partnership with 38 health facilities in Kathmandu valley to obtain cancer registry data on regular basis, while the registry also receives data from other inter/national sources like B.P Koirala Memorial Cancer Hospital, Chitwan and Tata Memorial Hospital, India. POPULATION COVERED: The Kathmandu valley PBCR covers 21 urban/rural municipalities of Kathmandu, Bhaktapur and Lalitpur districts with an estimated population of 30,71,932 in 2018. The registry predominantly represents the urban region of the country. REGISTRATION METHODOLOGY: The registry has used both the active and passive method of data collection. There are two major approaches to collect the registry data in the field. The first one is through the health facilities that includes data collection from the cancer and/or the general hospitals having diagnostic and cancer treatment facilities, pathology laboratories, hospices, ayurvedic centers and social security sections. The next is through the communities where the health coordinators, health in-charges and the female community health volunteers (FCHVs) at urban/rural municipalities have been oriented on PBCR. The FCHVs collect data through household visits in the given populations and submit them to the health in-charges, while the in-charges submit the data to the health coordinators, and the health coordinators directly to the NHRC office on monthly basis. Beside this, in places with very less reporting of cancer cases and low incidence rate compared to the estimated incidence rates for Nepal, the data enumerators are trained and mobilized in the communities. They personally visit the health coordinators, health post in-charges, female community health volunteers, ward chairpersons and community leaders to identify the cancer cases and then visit the particular households to collect the information. Then, the obtained data from all these sources are verified for the completeness, accuracy and residence followed by the entry into the CanReg5 Software at the NHRC office. Executive Summary FINDINGS: In 2018, out of 11,600 cancer cases obtained by Kathmandu Valley PBCR, a total of 2156 new cancer cases were registered (999 males and 1157 females). The Age Adjusted Incidence Rate (AAR) for male was 95.3 per 100,000 populations and for females, 98.1 per 100,000 populations. Similarly, 670 death cases due to cancer were registered in 2018. The Age Adjusted Mortality Rate (AAMR) for male was 36.3 per 100,000 populations (365 cases) and for female, 27.0 per 100,000 populations (305 cases). The mortality to incidence ratio (M/I) was 31%.The Government of Nepal is facing challenges in collecting death information since the cause of death as cancer is not registered by Civil Registration and still people feel reluctant to share cause of deaths including of cancer. The community-based approach followed by the PBCR has helped to get information on death cases in community; however, some death cases might have been missed in the registry. In Kathmandu Valley, the leading sites of cancer in males have been found to be lungs, stomach, urinary bladder, gallbladder and Non-Hodgkin's Lymphoma. Both the cancer incidence and mortality are highest in 70-74 years age group. In females, the commonest sites are breast, lungs, cervix uteri, gallbladder and ovary with the peak age of incidence in them is above 75 years followed by the age group of 65-69 years, and it is same for cancer death. Being the first year of registry, the unknown primary cases were only 4.5% in males and 3.2% in females indicating the good quality of the registry. However, with the improvement in record keeping and diagnostic and treatment facilities, the unknown primary cases will be minimized in future. In 90.5% of the cancer cases registered had microscopic basis of diagnosis. Remaining cases were registered based on non-microscopic ways like clinical, radiology, verbal information and Death Certificate Only. With the improvement in record keeping and continuation of registry, cases registered through non- microscopic basis will be reduced in future. Due to lack of scientific technique of data recording and reporting in health facilities and lack of culture in reporting in civil registration, Kathmandu Valley PBCR incurs extra cost/burden in terms of man, money, time and materials; as for the residence, the registry cannot fully rely on the residence address given by the sources. Hence, each individual patient/relative are contacted to confirm the residence. Therefore, it is recommended to have digital and uniformed medical recording system with determined mandatory variables in all government and private health facilities. Similarly, the death registration system needs to be strengthened and improved with the inclusion of cancer as a cause of death. The MoHP, concerned provincial government and local authority are recommended to develop area specific cancer prevention and control policy and interventions based on the evidence provided by the registry.